Development of Arabic Language Learning Media with The Content-Based Instruction for Students with Disabilities in Inclusive Schools - Shodiq, Muhammad Jafar; Ziihah, Rahil Ayu Na (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
One of the problems in the implementation of the Constitution of the Republic of Indonesia No. 8 of 2016 Article 6 Paragraph 10 concerning equal rights to education for people with disabilities is the absence of Arabic language learning media that can be accessed by the visually impaired. Therefore, learning media that suits their needs is needed, using relevant materials and approaches, especially the CBI (Content-Based Instruction) approach. This study aims to develop and evaluate CBI-based Arabic language learning media for visually impaired students at MAN 2 Sleman Yogyakarta. Research and development (RD) methods with a quantitative approach were used, involving expert evaluations and effectiveness tests on grade 10 students. Data is collected through tests, questionnaires, interviews, observations, and documentation. The media results developed are in the form of an Android-based application with audio features from native speakers, including three chapters of material and practice questions. The analysis of pre-test and post-test scores with paired sample T-test and N-Gain showed an improvement in students' Arabic language skills, with a significance value of 0.037 and an N-Gain score of 62.57%.